DIAGNÓSTICO DAS CADEIAS DO AGRONEGÓCIO DE ALIMENTOS E O ESTUDO DAS ESTRATÉGIAS COMPETITIVAS DO SETOR - Riedner, Karin; Sparemberger, Ariosto; Büttenbender, Pedro L.; Zamberlan, Luciano (Salão do Conhecimento, 2013)
Resumo